Function, evolution, and structure of J-domain proteins - Kampinga, Harm H.; Andreasson, Claes; Barducci, Alessandro; Cheetham, Michael E.; Cyr, Douglas; Emanuelsson, Cecilia; Genevaux, Pierre; Gestwicki, Jason E.; Goloubinoff, Pierre; Huerta-Cepas, Jaime; Kirstein, Janine; Liberek, Krzysztof; et al. (Cell stress & chaperones, 2018)
Hsp70 chaperone systems are very versatile machines present in nearly all living organisms and in nearly all intracellular compartments. They function in many fundamental processes through their facilitation of protein (re)folding, trafficking, remodeling, disaggregation, and degradation. Hsp70 machines are regulated by co-chaperones. J-domain containing proteins (JDPs) are the largest family of Hsp70 co-chaperones and play a determining role functionally specifying and directing Hsp70 functions. Many features of JDPs are not understood; however, a number of JDP experts gathered at a recent CSSI-sponsored workshop in Gdansk (Poland) to discuss various aspects of J-domain protein function, evolution, and structure. In this report, we present the main findings and the consensus reached to help direct future developments in the field of Hsp70 research.